2017
DOI: 10.1159/000456668
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Maternal Obesity on Foetal Growth and Metabolic Health of the Offspring

Abstract: Maternal and placental conditions that are unfavourable for the embryo/foetus have long-lasting effects on different tissues and functions of the body, which may persist for life and, potentially, also be transmitted to the offspring. This review resumes current evidence on principle maternal and gestational conditions associated with unfavourable metabolic programming of the offspring, along with their mechanisms of action, either supposed or already proved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 35 publications
0
27
0
2
Order By: Relevance
“…Several studies have shown that MO during gestation is an important determinant of offspring weight (Villamor & Cnattingius, 2006;Samuelsson et al 2008;Zambrano et al 2010;Maffeis & Morandi, 2017;Wang et al 2019). We have previously reported that even when MOF 1 eat a normal control laboratory diet, they exhibit increased body weight, fat and adiposity index (Zambrano et al 2010;Vega et al 2015).…”
Section: Discussionmentioning
confidence: 88%
“…Several studies have shown that MO during gestation is an important determinant of offspring weight (Villamor & Cnattingius, 2006;Samuelsson et al 2008;Zambrano et al 2010;Maffeis & Morandi, 2017;Wang et al 2019). We have previously reported that even when MOF 1 eat a normal control laboratory diet, they exhibit increased body weight, fat and adiposity index (Zambrano et al 2010;Vega et al 2015).…”
Section: Discussionmentioning
confidence: 88%
“…The offspring of obese, but not normal-weight mothers in another study demonstrated downregulation of the glycolysis pathway (p=0.049) 55 . Recent research showed that increase in hepatic gluconeogenesis was a major source of the total maternal glucose used by the fetus 56 . Interestingly, 1,5-anhydrosorbitol, which has been shown to be a maternal marker of short-term glycemic control, was observed in our cord blood study as a marker too, likely from maternal origin.…”
Section: Discussionmentioning
confidence: 99%
“…The concern with obesity is increased by the fact that some data show that genes play an important role in predisposing individuals to obesity, showing that having one or both of the obese parents, especially the mother, increases the risk of obesity in the offspring [23]. Women who are overweight or obese when they enter pregnancy are more likely to have children more likely to develop obesity during childhood, adolescence, and adulthood [24].…”
Section: The Etiology Of Obesitymentioning
confidence: 99%